Table top nanopatterning with extreme ultraviolet laser illumination - Attwood, D. T., author; Chao, W., author; Anderson, E. H., author; Iemmi, C., author; Rocca, J. J., author; Menoni, C. S., author; Patel, D., author; Marconi, Mario Carlo, author; Wachulak, P., author; Capeluto, M. G., author; Elsevier B. V., publisher (Colorado State University. Libraries, 2007)
Patterning with extreme ultraviolet light generated by a compact, bright laser source operating at a wavelength of 46.9 nm is demonstrated using two complementary approaches: multiple beam interferometric lithography and de-magnifying projection. Features with sizes ranging from 370 nm to 60 nm were printed in a few seconds in poly-methyl methacrylate resist. These proof-of-principle experiments demonstrate practical table-top nanopatterning tools based on extreme ultraviolet lasers for nanotechnology applications.
Keywords: interferometric lithography; nanopatterning; EUV lasers; table top photolithography